Effect of Tuna Bone Flour Crispy Biscuits Consumption on Height Growth of Children 12 - 48 Months - Pascoal, Meildy E.; Sahelangi, Olfie; Kristianto, Jusuf (Jurnal Health Sains, 2023)
Short birth length in children indicates a lack of nutrients consumed by the mother during pregnancy, so that fetal growth is not optimal and results in short birth length. Research Objective: to determine the effect of consumption of crispy biscuits of tuna fish bone meal on height growth in children aged 12-48 months. Quasy experimental design with pre-test-post test design using paired t-test. The results of the proximate test of crispy biscuits of tuna fish bone meal moisture content 4.41%, ash content 11.19%, carbohydrate content 47.64%, protein content 6.40%, fat content 30.36%, calcium content 7038. 70 mg/kg, phosphorus 0.91 mg/kg, potassium 2700.93 mg/kg, iron 60.73 mg/kg. The average height of children in the intervention group d crispy biscuits of tuna fish bone flour pre test 78.43 cm and post test 80.17 cm with a difference of 1.74 cm, control group pre test 88.84 cm and post test 89.84 cm with a difference of 1.01 cm. The results showed that there was a significant difference in the pre-test-post test of giving crispy biscuits of tuna fish bone meal on children's height (p = 0.03 <0.05). The conclusion is that giving crispy biscuits with tuna fish bone meal can increase height in children